Breeding and reproduction of transgenic fish fluorescent in captivity: a prospective scope - Scotto Espinoza, Carlos (2012)
The introduction, breeding and hybridization of fluorescent transgenic fish in Peruvian territory has been going since 2006 as demonstrated in laboratory tests reported in this article. He has spoken to Peru Law No. 29811 establishing the moratorium on the production of income and living modified organisms into the country for a period of 10 years for cultivation or breeding, including water, to be released into the environment. The paper shows the existence of aquatic LMOs that are being propagated commercially by aquarists and / or ornamental fish farmers out of control and could potentially be released into the environment. However, preliminary results on the other side could initiate a first analysis and risk management at the laboratory and / or under controlled conditions with these organisms (zebra fish case) that could provide the basis for future decision making relevant to the introduction of GMOs for any scientific purpose, commercial, environmental or other national interest not yet glimpsed.